2019
DOI: 10.1159/000501309
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Post-Endoscopic Retrograde Pancreatography Pancreatitis: A Retrospective Chart Review in a Regional Hospital in Japan

Abstract: Background: Endoscopic retrograde pancreatography (ERCP) is sometimes complicated by post-ERCP pancreatitis (PEP), which is a severe adverse effect. Objective: The present study was performed to (i) evaluate the risk factors for PEP and (ii) compare the risk of PEP after ERCP performed in the off hours versus regular hours. Methods: This retrospective study included 374 patients who underwent ERCP from January 2013 to December 2017. Among these patients, 38 (10.2%) developed PEP. The potential risk factors for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
4
9
0
1
Order By: Relevance
“…A recent Japanese study indicated that the incidence of post-ERCP pancreatitis was 10.2% (38/374), which was similar to the rate in our study (pancreatitis appeared in two patients) 24 . There was no evidence of biliary bleeding or perforation in our study, and it is unclear why elbow forceps insertion into the bile duct contributed www.nature.com/scientificreports/ to post-ERCP pancreatitis.…”
Section: Discussionsupporting
confidence: 91%
“…A recent Japanese study indicated that the incidence of post-ERCP pancreatitis was 10.2% (38/374), which was similar to the rate in our study (pancreatitis appeared in two patients) 24 . There was no evidence of biliary bleeding or perforation in our study, and it is unclear why elbow forceps insertion into the bile duct contributed www.nature.com/scientificreports/ to post-ERCP pancreatitis.…”
Section: Discussionsupporting
confidence: 91%
“…PEP is the most common complication after ERCP, and its risk factors are divided into patient-related and operationrelated factors. Female and patients with a history of pancreatitis are patient-related risk factors of PEP, while precut sphincterotomy, non-dilatation of the CBD, and di cult biliary cannulation are operation-related risk factors of PEP [5,14,15,[22][23][24]. In our study, the proportion of female patients in the asymptomatic group (64.6%) was higher than that in the symptomatic group (51.8%), and the difference was statistically signi cant (P = 0.031).…”
Section: Discussionmentioning
confidence: 99%
“…The propensity score was calculated using a multivariable logistic regression model. The following patients' characteristics which were reported as risk factors for ERCP-related complications were included in the model: age, gender, periampullary diverticulum, non-dilated CBD, history of pancreatitis, precut sphincterotomy, EST, ERBD, di cult cannulation, using anticoagulants before ERCP [14][15][16][17][18][19]. By using these propensity scores, patients in the asymptomatic CBD stones group were matched at a 1:4 ratio with those in the symptomatic CBD stones group.…”
Section: Matching Methods and Statistical Analysesmentioning
confidence: 99%
“…Therefore, we designed a clinical trial to investigate this. The majority of cases of PEP are mild and uncomplicated; however, severe pancreatitis accounts for up to 30% of cases (22)(23)(24)(25). In the current study, all patients presented with mild or moderate pancreatitis, and there was no clinical evidence of severe pancreatitis occurring.…”
Section: Discussionmentioning
confidence: 43%